The ultimate top secret guide to taking over the world - Nesbitt, Kenn (Sourcebooks Jabberwocky, 2011)
Contains tips and guidance to become an evil genius, equip an underground lair, dress for conquest, build a doomsday device, defeat secret agents, design an evil trademark, and take control of the world.